Globalization and Notary Authority In Making Agreements in The Era Industrial Revolution 4.0 - RINA, RINA; Hernoko, Agus Yudha; Sembiring, Rosnidar; Purba, Hasim (Ultimate Journal of Legal Studies, 2023)
The industrial revolution in the era of globalization greatly influenced the authority and practice of notary in the future and became an interesting issue. Developments in technology (information) are the result of human intellectual works that have brought extraordinary change in human lifestyle. The purpose of this research to determine the impact of globalization regarding the authority of a notary and the responsibilities of a notary and the ideal authority in developing and completing the authority and services of a notary in the era of the industrial revolution 4.0. Notaries play a role in carrying out some of the public functions of the state in the field of civil law which carry out legal services to people/public who have responsibilities regarding authentic evidence in the form of letters, deeds or documents made in writing for various legal actions, agreements and stipulations law or other authorities based on the will and requests of the parties. The research method used is normative juridical by reviewing and analyzing legal materials in the form of notary regulations using library research. The results of this study are that currently notaries in Indonesia are still bound by Indonesian Notary Act namely Undang Undang Jabatan Notaris(shorten UUJN) which is no longer fulfill with the needs of the development of globalization. The authority of notary services and practices as a result of the impact of globalization is a challenge and opportunity for the development and improvement of the future of the profession and position of a notary with the support of information technology which must be regulated by the state through amendments to UUJN.